2021
DOI: 10.3389/fpsyt.2021.649276
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Psychometric Properties of the Persian Version of the 21-Item Game Addiction Scale With a Sample of Adolescents and Young Adults

Abstract: Background: Excessive gaming has become a psychological health issue for both gamers and their social environments. This observation holds true for western but also non-western countries such as Iran. The aim of the present study was to translate and validate a Persian version of the Game Addiction Scale 21 (GAS 21) using a sample of adolescents and adults.Methods: A total of 412 participants (mean age: 22.16 years; 55.3% females) took part in the study. They completed questionnaires covering sociodemographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
1
4
0
1
Order By: Relevance
“…In this study, we also tested the relationship between the DLB Scale and scales assessing the dysfunctional use of ICTs. In line with the literature [ 34 , 35 ], DLB scores appeared to be negatively associated with ICT addiction levels measured with the BSMAS scale (r = −0.40), the Gaming Addiction Scale (r = −0.23), the Internet Addiction Scale (r = −0.42), and the SABAS scale (r = −0.38).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we also tested the relationship between the DLB Scale and scales assessing the dysfunctional use of ICTs. In line with the literature [ 34 , 35 ], DLB scores appeared to be negatively associated with ICT addiction levels measured with the BSMAS scale (r = −0.40), the Gaming Addiction Scale (r = −0.23), the Internet Addiction Scale (r = −0.42), and the SABAS scale (r = −0.38).…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, since low levels of balance appear to be linked to dysfunctional use of ICTs [ 18 , 32 , 33 ], we expected high levels of DLB to be negatively associated with scores on scales measuring online addictions [ 34 , 35 ], whether it be an addiction to social media, smartphones, the internet in general, or gaming activity. Therefore, we formulated four hypotheses regarding the external validity:…”
Section: Aim and Hypotheses Developmentmentioning
confidence: 99%
“…To the best of the authors' knowledge, these tools have been validated among Iranian adolescents; GAS-21 [33], GAS-7 [34], IGDS-SF9 [35], and POGQ [36]. The cut-off point for GAS-21 is unclear [37], the theoretical basis of the GAS-7 and IGDS-SF9 is DSM-5 [34,35], and POGQ assesses problematic online gaming, which covers five out of nine criteria of DSM-5 [37].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this increase, it is believed that addictive internet use has increased among young people and adults (Ostovar et al, 2021). With respect to Iran, there is growing evidence that too much screen time and web gaming have become major public wellbeing concerns (Abdoli et al, 2021). Moreover, recent empirical research evidence has shown an association between addictive disorders and adult attachment styles (D’Arienzo et al, 2019; Shaver et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this increase, it is believed that addictive internet use has increased among young people and adults (Ostovar, Bagheri, Griffiths, & Mohd Hashima, 2021) As respects the circumstance in Iran, there's expanding evidence that too much screen time and web gaming have gotten to be major public wellbeing concerns (Abdoli et al, 2021).…”
mentioning
confidence: 99%